2022
DOI: 10.1021/acsami.2c08834
|View full text |Cite
|
Sign up to set email alerts
|

Tailored Plasmonic Ru/OV-MoO2 on TiO2 Catalysts via Solid-Phase Interface Engineering: Toward Highly Efficient Photoassisted Li–O2 Batteries with Enhanced Cycling Reliability

Abstract: The photoassisted electrochemical reactions are considered an effective method to reduce the overpotential of Li–O2 batteries. However, achieving long-term cell cycling stability remains a challenge. Here, we report a solid-phase interfacial reaction (SPIR) strategy that introduces both oxygen vacancies (OV) and metal centers (Ru) into the MoO2 to synthesize the surface plasmon (i.e., Ru/OV-MoO2). Then, Ru/OV-MoO2 can be uniformly loaded on the TiO2 nanowires by the hydrothermal method. The plasma effect of Ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…(a,b) EIS plots of TiO 2 /CC and Ru/O V -MoO 2 /TiO 2 /CC before (a)/after (b) the discharge process under the light. Reproduced with permission from ref . Copyright 2022, American Chemical Society.…”
Section: Photocatalyst Of Light-assisted Metal–air Batteriesmentioning
confidence: 99%
See 2 more Smart Citations
“…(a,b) EIS plots of TiO 2 /CC and Ru/O V -MoO 2 /TiO 2 /CC before (a)/after (b) the discharge process under the light. Reproduced with permission from ref . Copyright 2022, American Chemical Society.…”
Section: Photocatalyst Of Light-assisted Metal–air Batteriesmentioning
confidence: 99%
“…101 Xing's research group found that TiO 2 /CC had a slower charge migration, resulting in the generation of more insulation discharge products and an increase in impedance after discharge, while Ru/O V -MT/CC remained stable (as shown in Figure 10a,b). 71 It is expected that as the number of discharges increases, the accumulation of byproducts in the electrode will lead to a further increase in impedance, resulting in a decrease in battery life. 102 The morphology of the semiconductor also affects impedance.…”
Section: Organic Polymermentioning
confidence: 99%
See 1 more Smart Citation
“…10−17 As one of the candidates in the spotlight, the Li−air(O 2 ) battery shows a high energy density of 3500 Wh kg −1 . 18 However, in the air environment, the existence of CO 2 inevitably results in the formation of side Li 2 CO 3 products due to its high solubility in organic electrolytes. 19 Developing the Li-CO 2 /O 2 battery with an energy density of 2100 Wh kg −1 can not only help investigate the growth and decomposition behavior of Li 2 CO 3 but also combine CO 2 resource utilization and energy storage.…”
Section: Introductionmentioning
confidence: 99%
“…Energy crisis and environment pollution are two focuses of international issues. Lithium-ion batteries (LIBs), widely used in various electronic devices such as cellphone and electric vehicles, can no longer satisfy the energy demand of ever-increasing mileage limited by their low energy density (<350 Wh kg –1 ). To solve this problem, advanced high-energy-density battery systems are urgently required and are gradually being considered. As one of the candidates in the spotlight, the Li–air­(O 2 ) battery shows a high energy density of 3500 Wh kg –1 . However, in the air environment, the existence of CO 2 inevitably results in the formation of side Li 2 CO 3 products due to its high solubility in organic electrolytes .…”
Section: Introductionmentioning
confidence: 99%